2013
DOI: 10.3390/molecules181012707
|View full text |Cite
|
Sign up to set email alerts
|

Heteroaryl Chalcones: Design, Synthesis, X-ray Crystal Structures and Biological Evaluation

Abstract: Chalcone derivatives have attracted increasing attention due to their numerous pharmacological activities. Changes in their structures have displayed high degree of diversity that has proven to result in a broad spectrum of biological activities. The present study highlights the synthesis of some halogen substituted chalcones 3(a-i) containing the 5-chlorothiophene moiety, their X-ray crystal structures and the evaluation of possible biological activities such as antibacterial, antifungal and reducing power ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…The ability of the test samples, in addition to the standard anti-oxidant butylated hydroxyltoluene (BHT), on DPPH radical scavenging was estimated according to the method described earlier [14,15]. Compounds of different concentrations were prepared in ethanol, 1 mL of each compound solution having different concentrations (10-250 μg/mL).…”
Section: Dpph Radical Scavenging Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of the test samples, in addition to the standard anti-oxidant butylated hydroxyltoluene (BHT), on DPPH radical scavenging was estimated according to the method described earlier [14,15]. Compounds of different concentrations were prepared in ethanol, 1 mL of each compound solution having different concentrations (10-250 μg/mL).…”
Section: Dpph Radical Scavenging Assaymentioning
confidence: 99%
“…The synthesized compounds were screened for ferric reducing power anti-oxidant ability by the method described earlier [14,15]. The method is based on the reduction of ferric (Fe 3þ ) to ferrous (Fe 2þ ), which is accomplished in the presence of antioxidants.…”
Section: Ferric Reducing Anti-oxidant Power (Frap) Assaymentioning
confidence: 99%
“…Compounds M 2 and M 6 exhibited significant protection activities against TMV at 500 μg/mL, with the values of 68.6% ± 7.7% and 72.3% ± 5.2%, respectively, which were even better than that of Ribavirin (51.8% ± 2.3%). The inactivation activities of compounds M 2 , M 6 , M 8 , M 10 , and M 14 at 500 μg/mL were 82.1% ± 4.1%, 83.2% ± 4.4%, 85.6% ± 2.6%, and 85.1% ± 3.6%, respectively, which were better than that of Ribavirin (72.9% ± 2.4%). Based on the previous bioassays, the 50% effective concentration (EC50) values of protection activities against TMV of the title compounds were tested and presented in Table 2.…”
Section: Antiviral Activity Screening Of Title Compounds Against Tmv mentioning
confidence: 85%
“…Chalcones, belonging to the flavonoid family and obtained from Carthamus tinctorius first, possessed a broad spectrum of biological activities, including antibacterial [9][10][11][12], antifungal [13], anti-Alzheimer's disease [14], anticancer [15], antitrichomonal [16], and anti-trypanosomacruzi [17] activities. It is reported that Verma et al, had reported a series of chalcones derivatives, which were used to control plant viruses [18].…”
Section: Introductionmentioning
confidence: 99%
“…Chalcones are bicyclic flavonoids that consist of two aromatic rings that are linked by an α,β‐unsaturated ketone system . They display several pharmacological activities such as antibacterial, antifungal, antileishmanial, and antitumor . Recently, many derivatives of chalcones were synthesized for evaluation of their cytotoxic activity.…”
Section: Introductionmentioning
confidence: 99%